Virtual forums: a pedagogical tool for collaboration and learning in teacher education - Espitia, Maria Isabel; Clavijo Olarte, Amparo (Colombian Applied Linguistics Journal, 2011)
Implementing technological tools in EFL classes has not been easy for language teachers, they often struggle to make class activities consistent with the curriculum, policies, students’ needs and likes and lately, with computer and internet-based ICTs. The problem regularly is that EFL teachers do not possess the pedagogical and technological knowledge to use technological tools to foster communication and interaction among students to learn collaboratively. This study deals with a teacher education experience in which tools such as blogs, learning software, e-mail, forums and internet-based tools were used to improve EFL learning and teaching. Data were gathered from the group of EFL teachers in two phases: the first phase included participants’ planning, discussion, and implementation of a pedagogical project for young EFL learners; the second phase consisted of the participants’ reporting and evaluating their performance using forums and blogs with their students. The study demonstrated that teacher education experiences are crucial for teacher learning to integrate the use of forums and blogs in the EFL Curriculum. It also showed that the use of blogs and forums requires addressing language pedagogy from a perspective that values communication, collaboration and participation as central elements of learning.